PREFACE, TABLE OF CONTENTS, & ACKNOWLEDGMENTS - Herdiansyah, Herdis (UI Scholars Hub, 2018)
Journal of Environmental Science and Sustainable Development (JESSD) is an international, interdisciplinary, double-blind peer-reviewed, and open-access journal established in 2018. Published by School of Environmental Science of Universitas Indonesia (http://sil.ui.ac.id/), the JESSD provides an opportunity for academics, practitioners, and community representatives to examine, exchange, and reflect on a wide range of issues relating to environmental science and sustainable development in the developing countries especially in ASEAN region. On this first edition of the JESSD, we present eight papers with various topics related to the scope of the JESSD. Those eight papers are coming from different affiliations, including many different universities and organizations such as Tohoku University (Sendai), Asahi Group Holdings Ltd. (Ibaraki), Universitas Indonesia (Jakarta), Health Research and Development Unit (Central Java), Trisakti School of Tourism (Jakarta), University of Kitakyushu (Fukuoka), Kyoto University (Kyoto), and Institut Pertanian Bogor (Bogor). Those papers also enclose different issues, including sago as environmental friendly food resource, transportation of municipal solid waste, accounting for residual functions in comparative life cycle assessment, sustainable palm oil production, integrated waste management modelling, LCA in health service industry, welfare of elderly people in rural area, and implementation of temporary import procedure on electronic products. By presenting different issues from different affiliations hopefully will enrich the global discussion of environmental science and sustainable development.